Endogenous Secretory Receptor for Advanced Glycation End Products Protects Endothelial Cells from AGEs Induced Apoptosis. (10th April 2018) - Yang, Guomin; Huang, Yinqiong; Wu, Xiaohong; Lin, Xiahong; Xu, Jinting; Chen, Xiaoyu; Bai, Xuefeng; Li, Qiulan
Abstract : Endogenous secretory receptor for advanced glycation end products (esRAGE) binds extracellular RAGE ligands and blocks RAGE activation on the cell surface, protecting endothelial cell function. However, the underlying mechanism remains unclear. Endothelial cells overexpressing the esRAGE gene were generated using a lentiviral vector. Then, quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to assess esRAGE mRNA and protein levels, respectively. Hoechst-PI double staining was used to assess apoptosis. Western blot and qRT-PCR were used to assess the expression levels of apoptosis-related factors and the proinflammatory cytokine NF-кB. Compared with the control group, AGEs significantly induced endothelial cell apoptosis, which was significantly reduced by esRAGE overexpression. Incubation with AGEs upregulated the proapoptotic factor Bax and downregulated the antiapoptotic factor Bcl-2. Overexpression of esRAGE reduced Bax expression induced by AGEs and increased Bcl-2 levels. Furthermore, AGEs increased the expression levels of proinflammatory cytokine NF-кB, which were reduced after esRAGE overexpression. esRAGE protects endothelial cells from AGEs associated apoptosis, by downregulating proapoptotic (Bax) and inflammatory (NF-кB) factors and upregulating the antiapoptotic factor Bcl-2.